AN ELDERLY-CENTERED DESIGN APPROACH FOR MOBILE CHAT APPLICATION - Mahmud, Murni; NAHREEN ZANNAT; NADIA NOWSHIN (Journal of Information Systems and Digital Technologies, 2022)
Connection and communication are heavily contingent on the internet and mobile apps, especially in this pandemic. With the blessings of Information and Communication Technology (ICT), the population of this digital era are highly dependent on several mobile applications. Undoubtedly, mobile apps have made our life easier and more straightforward, especially in the communication sector. There are at least hundreds of chat applications worldwide. Most of these communication platforms have been developed with many interactive and complex features designed mainly for the younger generation. However, in the perspective of Bangladesh, the older generation is unfamiliar and less comfortable with the concept and lacks the necessary digital literacy to use these advanced communication platforms. They frequently encounter difficulties in comprehending and using those applications. Thus, the authors described human-computer interaction (HCI) and briefly discussed some of the design issues from older adults’ experiences in this report. Furthermore, a suitably designed chat application was proposed based on understanding the challenges faced by the elderly. With a user-centered approach, the design emphasizes simplicity and minimalism, making it easier for the elderly to communicate through mobile technology.